Anxiety in Chinese Patients With Cleft Lip and/or Palate: A Preliminary Study - Xie, Zhuojun; Yang, Chao; Zhao, Yuxi; Yang, Yichun; Xia, Weiyao; Zong, Yuan; Chi, Ting; Shi, Bing; Huang, Hanyao; Gong, Caixia (Frontiers in Pediatrics, 2022)
Objectives: To preliminarily analyze factors that affected the prevalence of anxiety in Chinese patients with cleft lip and/or palate (CL/P). Methods: The Generalized Anxiety Disorder Scale (GAD-7) was used to screen anxiety in Chinese CL/P patients. Non-CL/P individuals were also included as the control group. Sociodemographic and clinical data consisting of diagnosis, gender, only child or not, monthly household income, and current family location were collected to analyze possible factors that could affect the anxiety of this patient population. Results: 142 and 78 valid questionnaires were collected from the study and control groups, respectively. The mean GAD-7 score of the study group (3.092±3.381) was significantly lower than the control (3.987±2.505). Moreover, the proportion of patients presenting with moderate-severe anxiety was larger in the study group than in the control group (6.6% vs. 0.0%). Statistically significant differences in GAD-7 scores were observed between the study and control groups when the patient was the only child, living in an urban area, or the monthly household income was between 1,000-5,000 yuan. Conclusion: Although the severity of anxiety in Chinese CL/P patients was not severer than those without CL/P, there was a relatively high incidence of moderate-severe anxiety in CL/P patients, while the only child, current family location and the monthly household income played significant roles in affecting anxiety psychology.